The Effect of Surfactant on Polyherbal Liquid Shampoo and its Comparative Analysis - Surve Rashmi; Shivathaya Neha; Sawant Reshma; Bhat Madhura; Yashwant Devraj; Mane Vishal; Patil Rohit; Sidhaye Isha (International Journal of Ayurveda and Pharma Research, 2022)
Objective: Herbal shampoo is gaining immense popularity among all consumer groups due to rising awareness about the side effects of chemical formulations. It was also observed that not many marketed shampoos incorporated excellent hair nurturing properties of curry leaves. The aim of the study was to formulate and evaluate herbal shampoo using Murraya koenigii, Phyllanthus emblica, Acacia concinna Linn., Trigonella foenum-graecum, Sapindus mukorossi and perform a comparative analysis with marketed formulation. Method: Three formulations were prepared using extracts of Murraya koenigii, Phyllanthus emblica, Acacia concinna, Trigonella foenum-graecum and Sapindus mukorossi in definite proportions. Decyl Glucoside and Sodium Lauryl Sulphate were added as surfactant in adequate amount. The formulated shampoo was evaluated for organoleptic properties (colour and odour), pH, surface tension, viscosity, dirt dispersion, cleansing action, foaming ability and stability studies. Results: The formulated shampoos were brown in colour with good acceptable fragrance. All the formulations showed good cleansing and detergency power with stable foam. F1 showed comparatively better foaming ability. All the formulations had neutral pH and low surface tension (21-25 dyn/cm). The solid content was found to be in the range of 23-27 % and viscosity 4885 cP- 4903 cP. The results of the prepared formulations were compared with a marketed formulation and were found that F1 formulation was on par with marketed formulation. Conclusion: The prepared shampoo had good characteristics. It was further inferred that it is possible to develop safer and equally effective shampoo using ingredients of plant origin.